Respuesta agronómica de las plantas de café arábica (coffea arábica) a la aplicación de bonos edáficos y foliares - Pilatasig Pilaguano, Milton Fabricio (2017)
The research project was carried out in the experimental center “La Playita” of the technical university of Cotopaxi La Maná. This research is the experimental type as it promotes studing variables both in agronomic response and the planting of coffee with the application of two foliar and edaphic fertilizers. Coffee is one of the most popular products around the world. This preference has been awarded second place in the products of major economic importance woldwide.The quality of coffee depends on many factors, mostly include three areas: Farming, industrialization and storage. The determining factors in the crop are the kind of species and varieties, as well as agronomic and environmental conditions. The criteria used to establish coffee quality is the genetic variety, crop type and process of industrialization. The preset document aims to explore coffee processing and its treatments, also diseases and pests that attack during the pre and post -harvest.